Investigating the effects of operating parameters on the performance of sorption-enhanced membrane reactor for ethanol steam reforming reaction using computational fluid dynamics method - Zeynali, Rahman; Khalili, Seyede Sara; Pezeshki, Zahra; Akbari, Mona; Soleymani, Hosna; Samimi-Sohrforozani, Ehsan; Safaei, Babak (Aip Publishing, 2023)
In this study, the performance of a sorption-enhanced membrane reactor (SEMR) was examined using a Pd-Ag membrane during ethanol steam reforming (ESR). During this study, simultaneous ESR and CO2 adsorption concept was adopted and computational fluids dynamic (CFD) method (two-dimensional model) was developed to evaluate the SEMR performance during ESR reaction. The employed CFD model for the present study provided information about the molar fractions and pressures of components to analyze driving forces under unsteady state condition. Regarding validation, the experimental data related to the membrane reactor (MR) during ESR reaction showed good agreement with modeling outcomes and the application of adsorption reaction improved MR performance. The SEMR performance was investigated after model validation, and during this step, SEMR and MR were compared. Moreover, the effects of main operating parameters, such as gas hour space velocity (GHSV), reaction pressure, and temperature, were studied to compare the SEMR and MR performance during C2H5OH conversion and hydrogen recovery. CFD modeling results showed that SEMR had better performance and increased the ethanol conversion about 20% (SEMR: 70% and MR: 59%) by temperature enhancement at low pressures compared with the conventional membrane reactor. The relative error between numerical and experimental data obtained was 3% in this study.
Keywords: Hydrogen-Production; Catalytic Dehydrogenation; High-Selectivity; Cfd Analysis; Ethylbenzene; Pressure